Honeycomb-structured carbon aerogels from nanocellulose and skin secretion of Andrias davidianus for highly compressible binder-free supercapacitors. (1st October 2020) - Wang, Qunhao; Xia, Tian; Jia, Xiwen; Zhao, Jiangqi; Li, Qingye; Ao, Chenghong; Deng, Xueyong; Zhang, Ximu; Zhang, Wei; Lu, Canhui
Graphical abstract: Highlights: SSAD is used for nitrogen-doping of carbon aerogels from nanocellulose. The well dispersion of SSAD in water is realized with the assistance of CNC. Honeycomb-like structure of carbon aerogels is produced. The carbon aerogels show superelasticity and excellent electrochemical performance. Abstract: Nanocellulose-derived carbon is a promising material in energy storage because of its sustainability, low environmental impact, and large specific surface area. Herein, the skin secretion of Andrias davidianus (SSAD) is applied for the first time as the bio-nitrogen source to dope carbon aerogels from nanocellulose. Cellulose nanocrystal (CNC) is discovered to be very effective to address the dispersion problem of SSAD in water. After being homogeneously mixed with cellulose nanofiber (CNF), honeycomb-structured nanofibrous carbon aerogels are obtained via unidirectional freeze-drying of the SSAD/CNC/CNF mixture followed by high-temperature carbonization. Impressively, unlike those fragile carbon aerogels in many early works, the present ones exhibit outstanding elasticity in repeated compression and release tests. Moreover, a symmetric binder-free supercapacitor is assembled from the carbon aerogels, which exhibits improved electrochemical capacitive properties and cycling stability. And even after 500 compression and release cycles, the supercapacitor can still maintain high capacitive performance, indicating its superiorities in durability and electrochemical stability.